Reduction of liver abscesses in feedlot cattle by the addition of tannins on diet - Cabral, C. (2019)
Liver abscess is a common disorder of feedlot cattle developed usually after ruminal acidosis. Despite of this condition is generally asymptomatic, it causes economic losses due to the reduction of feed efficiency. Routinely, antibiotics have been used as growth promoters, which can control ruminal acidosis. However, these have not direct effect on liver abscess and their use in the food chain has been under revision because of the concern about the development of antibiotic resistance. Thus, the need of alternatives increases. Tannins have been used for growth promotion in fattening of cattle, but they have not been evaluated for controlling liver disease. The aim of this study was to evaluate the effect of plant-based tannins on the prevalence of liver abscess in feedlot cattle. Two groups of Angus heifers were fattened under regular feedlot conditions; one received the regular feed (control group (CG), n=237 cows) with monensin (40 g/tn of Dry Matter (DM)) as growth promoter. Feed of the other group (tannin’s group (TG), n=258 animals) was added with a commercial blend of tannins (2500 g/tn DM). Animals stayed in the feedlot until fattening was finished, and were sacrificed in the slaughterhouse. Presence of liver abscess was evaluated at the postmortem inspection. Additionally, one sample of the right lobe of healthy liver was collected for histopathologic examination of in approximately 20% of cows from both groups (69 from TG and 66 from CG). Macro and microscopic abscess development were compared by Fischer’s Exact Test. A numeric score of microscopic changes was used and differences in microscopic liver affection between groups were evaluated with the Mann- Whitney test. Differences for all statistics were considered significant when p<0.05. Three animals from TG and 14 from CG showed abscesses, being this difference significant (p=0.0051). Microscopically, there was no difference since 35 animals from TG and 33 from CG showed microscopic abscess (p=1). Finally, there were no differences in microscopic scores from both groups (p=0.7452). The obtained results suggested that the tannin treatment is effective in controlling the development of liver abscess. However, presence of microscopic lesions in cows from TG suggested that the treatment regulated their progression but not the colonization of liver by the infectious agents. Nevertheless, the mechanisms involved are unknown and should be determined in further studies.